Making a difference for kids a guidance activity resource book - Jara, Lito S. (Quezon City New Day Pub., 1998)
Purpose: A book that is intended for teachers, parents, and especially counselor that would "serve as an instrument to enable you to reach out to each young person in your care."
Contents: Games. Stories. Showing emotions. Being part of a family. Pictures. Drawings. Study habits. Credits. Postscript.
Keywords: Home room guidance (Elementary) -- Philippines -- Handbooks, manuals, etc; Children -- Counseling of -- Philippines -- Handbooks, manuals, etc; Counseling in elementary education -- Philippines -- Handbooks, manuals, etc